PRE-ALPINE MIGMATITIC ROCKS AND ACID TO INTERMEDIATE ORTHOGNEISSES IN PENTELIKON MOUNTAIN (NE ATTICA, GREECE) - Baziotis, I.; Mposkos, E.; Perdikatsis, V. (Bulletin of the Geological Society of Greece, 2004)
In the broad area of Pentelikon Mountain, which is part of the Attic-Cycladic crystalline belt, metamigmatites and orthogneisses occur as tectonic slices within the calc-schists or between calcschists and marbles. In the metamigmatites relic of migmatitic fabrics, comprising leucosomes and melanosomes, and cross-cutting aplitic and pegmatitic dykes are still preserved. The orthogneisses have dioritic to granitic composition. They are interpreted to be probably formed in a magmatic arc setting. Granitic orthogneisses show high-K contents and are enriched in LILEs and depleted in HFSEs. They also exhibit fractionated REE patterns with slight to strong negative Eu anomaly. The exceptionally high K2O contents (>7%) and the very low Na2Û contents (0.4-0.98 wt%) of certain phengite-orthogneisses with ultramylonitic textures are attributed to metasomatic processes that occurred during ultramylonitization.